PENGARUH SIKAP KEUANGAN, PERILAKU KEUANGAN, DAN LITERASI KEUANGAN TERHADAP MINAT MENABUNG ANGGOTA KPN SUSILA BHAKTI - SUGIANTARI, NI KOMANG; SANJAYA, NI MADE WULAN SARI (GANEC SWARA, 2024)
This research aims to analyze the influence of financial attitudes, financial behavior and financial literacy on the interest in saving of members of the Susila Bhakti Civil Service Cooperative. This research uses a quantitative approach with data collected through distributing questionnaires. Questionnaire measurements use a Likert scale with a scale from 1-5. The selection of respondents used a non-probability sampling method, namely sampling used by researchers accidentally or who happened to meet the researcher at that time. Determining the number of samples used the Slovin formula with the number of respondents used being 70 respondents. The data analysis technique used to assist this research uses the SPSS version 18 model. The results of this research are that all the variables studied including financial attitudes, financial behavior and financial literacy have a positive and significant influence on interest in saving, and financial literacy is able to moderate financial attitudes. on the interest in saving of members of the Susila Bhakti Civil Servant Cooperative. Members of the Civil Servant Cooperative are expected to always be wise in responding and behaving with their finances and can increase their financial literacy in order to stimulate interest in saving. Abstrak berbahasa inggris terjemahan dari abstrak berbahasa indonesia